Phylogeographic origin determination of Helicobacter pylori strains from a Colombian cohort by multilocus sequence typing (MSLT) (2018)
Helicobacter pylori is a gram-negative bacterium associated to diverse pathologies ranging from gastritis to gastric cancer. Due to its clinical and evolutionary importance, there has been extensive research focused on its transmission mechanisms, population genetics and phylogenetic relationships among different H. pylori isolates world-wide. Until now, population genetic studies have focused on the amplification of 7 different housekeeping genes using Multilocus Sequence Typing (MLST). With this technique, a correlation between the ancestry of H. pylori and the risk of developing a severe pathology like gastric cancer has been reported. In Colombia, this type of research has been done mainly in patients from the cities in the Andean and Pacific Regions (Túquerres and Tumaco, respectively). However, to our knowledge, in Bogotá, the capital of Colombia, there have been only two MLST studies. For this reason, in the present study we determined the ancestry of 52 H. pylori strains obtained from a cohort of symptomatic patients infected with this bacterium from Hospital Fundación Santa Fe de Bogotá. Additionally, to adress whether a correlation exists between the ancestry of H. pylori, the presence of the cytotoxin- associated gene A (cagA) and pathology of each patient, the cagA was amplified for all strains. This analysis showed that all strains evaluated belonged to the hpEurope group and there was no correlation with the cagA gene presence and the severity of the pathology for our sampled population. We complemented these results with the analysis of several Latin American Strains published recently, finding a clustering of the isolated strains with other Colombian strains creating a distinct group from those isolated in Nicaragua and Mexico.